EFEK MEDIA SOSIAL TERHADAP REMAJA SEBAGAI SUMBER IDE PENCIPTAAN KARYA SENI LUKIS - Hasanudin, Miftah; Rahman, Deni (Institut Seni Indonesia Surakarta, 2022)
The effect of social media on adolescent is the main discussion on the background of magnitude of the influence of social media on daily life, such as patterns of interaction and development of ways of thinking of adolescent. Adolescent segment was chosen because it is the transition of a person to adulthood, this age is also called the age of shock where a person begins to enter the wider environment and relationships. The creation of this painting is expected to provide knowledge about the effect of social media on adolescent, as well as the process of creation and its visual aesthetics.